Contemporary Hispanic cinema : interrogating the transnational in Spanish and Latin American film - Dennison, Stephanie (Colección Támesis. Monografías, 2013)
This book focuses on the cross-currents and points of contact in film production among so-called Hispanic countries (Spain, Portugal and Latin America), and in particular the impact that co-production and supranational funding initiatives are having on both the film industries and the film of Latin America in the twenty-first century.